The independence of the Federal Reserve System - Clifford, A. Jerome (Philadelphia: University of Pennsylvania Press, 1965)
The book examines the independence of the Federal Reserve bank of United States. The ACT establishing it, its duties and responsibilities in managing the monetary policies of the country and roles in banking sectors and the economy at large.
Includes index
Bibliography: p. 400-416.
usc 27/09/2018
Loans
Keywords: Federal Reserve banks